Beyond the Breach: Building Trust through Integrated Security and Customer Relationship Management (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Customer information protection and maintaining people's trust are critical for any company. This paper focuses on the impacts of integrated security systems harmonizing customer relationship management (CRM) to ensure and maintain customers' trust. The paper provides step-by-step strategies showing how different organizations can address security breaches and improve customer relations. The implications of our study point to the fact that there is a strong positive interaction between security measures and CRM approaches on the one hand and the minimization of risks and building the long-term relationship between the firm and its customers on the other.